Prospects for the Development of the banking sector of Azerbaijan - Y. F. Veliyeva (Финансы: теория и практика, 2021)
The relevance of the problem of the banking sector development lies in the fact that banks, implementing their economic policy, can ensure continuous sustainable growth of the entire national economy. The study aims to offer long-term proposals for the development of the banking sector of Azerbaijan, which will bring it to the next level. During the research the author used such methods as the study of literary sources, analysis, synthesis, abstraction and special methods. The study presents six major macroeconomic factors that significantly affect the rate of the long-term growth of the banking sector: customer focus, legal framework, new banking technologies, cyber threats, use of the experience of large IT companies, and qualified personnel. The author analyzed the effects of these factors on the long-term growth rate. Recommendations are given on the use of innovation and advanced technologies for the benefit of development, that will allow building an efficient and competitive banking system. Based on the results of the study, the author formulated proposals for improving the banking sector of Azerbaijan that will bring it to the next level. In particular, it is proposed to optimize robotic process automation, namely, to completely revise the existing methods of work, and not just solve problems using robotization. The author concluded that there is a long way ahead towards ensuring the sustainable development of the banking sector in Azerbaijan, which is currently at the beginning of its journey. Further research on this topic will allow a deeper study of digital opportunities and prospects for the integrated implementation of innovation.